ASSESSMENT OF LOWER URINARY TRACT SYMPTOMS IN BENIGN PROSTATIC HYPERPLASIA TREATED BY CONSERVATIVE MANAGEMENT - ANIL P SINGH,; SAURIN K MODI,; POOJA N RANPARIYA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to evaluate the effectiveness of prescribed drug therapy for patients with benign prostatic hyperplasia (BPH) and to analyze the quality of life (QOL) of these patients. Methods: A prospective observational study was conducted over 1 year, from October 2019 to September 2020, aiming to assess the effectiveness of medications used in BPH treatment. Urine flow was measured at each follow-up visit using an uroflow meter to evaluate treatment effectiveness. The American Urological Association’s QOL and the International Prostate Symptom Score (IPSS) were utilized to assess patients’ QOL. Results: Out of 250 patients screened, 138 were eligible for the study, with 82 (59.43%) in the 60–80 age group. A total of 1212 medications were prescribed, with alpha-adrenergic blockers and 5-alpha reductase inhibitors (5-ARIs) making up 34.08% of all prescriptions. Urine flow increased from 13.42 mL/s at the first visit to 14.46 mL/s at the second visit, reaching 15.62 mL/s by the third visit. The IPSS score decreased from 15.44 at the first visit to 13.51 at the second and further to 12.28 at the third. Conclusion: Alpha-adrenergic blockers such as tamsulosin (30.12%) and silodosin (3.96%), along with the 5-ARI dutasteride (0.50%), were prescribed for BPH treatment. A statistically significant improvement (p<0.05) in lower urinary tract symptoms and QOL was observed at each follow-up visit.